Analisis Bibliometrik Perkembangan Penelitian Terkait Integrated Sustainable Waste Management (Iswm) Tahun 2020-2024 Menggunakan Vosviewer - Agum Muladi; Samsul Hadi (JURNAL TAMPIASIH, 2024)
This bibliometric research focuses on mapping research with a database of research articles from the sciencedirect website. This research was conducted to determine the development of research in the field of waste management, especially integrated sustainable waste management. Data collection was carried out based on the sciencedirect database with the keyword "integrated sustainable waste management (iswm)", the publication category was research articles used as many as 1000 articles. Data retrieval was carried out using the sciencedirect website to obtain accurate research development data. Data analysis and visualization were conducted using VOSViewer. The results of the analysis show that the dominant research topics on integrated sustainable waste management include sustainability and circular economy. Integrated sustainable waste management has research potential and opportunities that are divided into 11 clusters with 103 items that include discussion of concepts, models, thoughts, approaches, effectiveness and efficiency of integrated sustainable waste management. This research is still limited by utilizing the sciencedirect website with some restrictions used to filter the data to be retrieved, then in retrieving metadata from using VOSViewer to create visualization of mapping and clustering of topics. Furthermore, this research can be a reference for other researchers who will examine the topic of integrated sustainable waste management.